DYNAMICS OF MOISTURE RELEASE FROM MAIZE HUSKS AS A FUNCTION OF CROP DENSITY - Tabakovic, Marijenka; Poštić, Dobrivoj; Živković, Ivana; Štrbanović, Ratibor; Kolarić, Ljubiša; Sečanski, Mile; Stanisavljević, Rade; Oro, Violeta (Journal on Processing and Energy in Agriculture, 2024)
Maize husk mass affects the dynamics of maize kernel moisture release as well as the yield and harvest timing of maize. This study aimed to observe the dynamics of moisture release in maize husks depending on the sowing density technology used. At the Zemu Polje location, a trail was established with three hybrids (H1-ZP 4708, H2-ZP4242, H3-ZP4790) in three densities (G1-40,816, G2-69,689, G3-89,286). During the vegetation period, 15 days after fertilization, four samples (V1-V4) were taken to determine the fresh and dry weight of the husk. The leaves were dried in an oven at 60°C for 12 hours. The effect of the genotype was reflected in the different masses of the maize husks and the dynamics of moisture loss. It was most pronounced in hybrid ZP 4242, which had the highest moisture loss between V1 and V4 samples at 9.86 %. It is also the hybrid with the highest fresh mass of leaves, 88.71 g. The dynamics of mass reduction, i.e. moisture loss, was linear in all hybrids, except for the exceptions by ZP 4242. The effects of sowing density and genotype on the moisture release of the maize husks and thus the maize kernel lead to an optimal harvest and a reduction in the risk of yield loss.